Milk yield and reproductive performance of hair goats raised under the extensive condition in konya and karaman regions of turkey - Mehmet Emin Tekin; Mehmet Arlı; Şahin Öztürk; Murat Öğeç (Eurasian Journal of Veterinary Sciences)
Aim: This study was conducted to investigate the characteristics of milk yield and reproductive performance of Hair goats raised under the extensive condition in Konya and Karaman regions of Turkey. Materials and Methods: For this purpose, 383 and 58044 records were analyzed for milk yield and reproductive performance, respectively. Six measurements were performed with 30 days intervals for evaluating of the goats? milk yield characteristics. Individual lactation milk yield was calculated as area under the lactation curve. General linear model involving factors of region, farm, goat age and birth type were used for milk yield characteristics in statistical analyses, Chi square test was employed for evaluating the reproductive performance. Results: The mean of the lactation period, daily and lactation milk yield, were found as 171.0 days, 753.7 mL, and 128.9 L, respectively. Despite the fact that the effect of birth type factor on all three characteristics was not significant (p>0.05), it was found that the region and farm factors had a significant effect on all three characteristics (p<0.001). Goat age factor had a significant effect on daily milk yield and lactation milk yield (p<0.001). Birth rate, twin rate, and kidding rate of goats were found as 81%, 9%, and 0.88, respectively. In reproductive performance, the significant difference between two regions and also significant differences among years in each regions were seen (p<0.01). Conclusion: In conclusion, the parameters of the lactation milk yield and lactation period in Hair goats raised in both regions were seen in higher value than the levels reported previously in the literature.